Analysis of household electricity expenditures among residents of suco leuro, lospalos administrative post, lautem municipality - Paulo Alves Cabral; Pedro Correia; Kristiani (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
In general, the population of Suco Leuro relies on electrical energy for daily activities, which is predominantly non-renewable and supplied by the state through the public utility company EDTL (Eletricidade de Timor-Leste). This electricity is purchased via prepaid systems at designated sales stations; however, consumers often overlook strategies for energy conservation. Therefore, this study aims to examine the patterns of electricity expenditure among households in Suco Leuro over a one-week period. This research was conducted to describe both the positive and negative effects observed in the field. The study employed a sample-based research design, involving 60 household heads as respondents in Suco Leuro, Lospalos Administrative Post, Lautem Municipality, during the 2023 academic year. The findings indicate that 100% of the population in Suco Leuro has had access to electricity since 2013 and has installed prepaid electricity meters. The analysis of the results shows that 28.3% of households consume between 2.1 and 9.45 kWh per week, 45% consume between 10.14 and 18.4 kWh per week, and 26.7% consume between 22.45 and 43.86 kWh per week. These findings suggest that higher electricity consumption is primarily influenced by the duration of appliance usage and the power capacity of electrical devices used by households.